Injustices in Black Maternal Health: A Call for Different Research Questions, Orientations, and Methodologies - Sealy-Jefferson, Shawnita (Frontiers in Public Health, 2022)
For decades, Black mothers have been most likely to suffer the worst outcomes of pregnancy, including death. Even though traditional individual level risk factors do not explain racial inequities in maternal morbidity, most studies identify Black race as a predictor, instead of the ways in which our society is structured around racism that makes Black mothers vulnerable to adverse health outcomes. As an example, the U.S is exceptional in incarcerating its residents, and Black men are six times and Black women are three times more likely than their white counterparts to be incarcerated. Relatedly, violent death caused by homicides disproportionately impacts Black communities, such that is the leading cause of death for males and females aged 10–34 years. Estimates suggest that more than 50% of urban residents know more than 10 murder victims, and approximately 200 people are affected by each neighborhood murder. Recent research has begun to shed light on the impacts of stressful neighborhood social conditions on risk of the adverse birth outcomes among Black mothers however, few studies have quantified the impact of macro-social neighborhood factors like violent death exposures and mass incarceration on Black maternal health. Future research that leverages relevant theoretical frameworks, is co-created and co-led with affected communities, and focuses on relevant neighborhood level traumas is warranted if we are to address the longstanding racial inequities in maternal health.